2008
DOI: 10.1007/s11033-008-9387-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymorphism in the leukemia inhibitory factor gene on litter size in Large White pigs

Abstract: DNA polymorphism of the porcine leukemia inhibitory factory (LIF) was investigated and used to study the effects on litter size in Large White pigs. A total of 2,167 litter records from 420 sows genotyped at two SNP loci (LIF1 and LIF2) within LIF gene were analyzed to determine whether LIF influenced total number born (TNB) and number born alive (NBA). The results indicated that B allele at LIF1 locus and A allele at LIF2 locus seem to have advantageous effects on litter size. However, the combined analyzed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Litter size results from a sequence of events starting with ovulation rate, fertilization rate, embryo survival and uterine capacity (Lin et al., ). Significant limits to litter size have occurred as a result of embryo losses before and during embryo implantation (Fu et al., ; Geisert & Schmitt, ; Lin et al., ; Wu, Wang, Li, Fu, & Zhao, ). Understanding the factors associated with embryo losses during implantation will be required to make advancements in litter size and would be aided with additional information on the genes and proteins involved in regulating embryo attachment and survival (Fu, Fu, & Wang, ; Ren, Guan, Fu, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Litter size results from a sequence of events starting with ovulation rate, fertilization rate, embryo survival and uterine capacity (Lin et al., ). Significant limits to litter size have occurred as a result of embryo losses before and during embryo implantation (Fu et al., ; Geisert & Schmitt, ; Lin et al., ; Wu, Wang, Li, Fu, & Zhao, ). Understanding the factors associated with embryo losses during implantation will be required to make advancements in litter size and would be aided with additional information on the genes and proteins involved in regulating embryo attachment and survival (Fu, Fu, & Wang, ; Ren, Guan, Fu, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, no association of IL-4R variants with the recurrent abortion has been reported in Iranian women [52]. Furthermore, the polymorphisms of the IL-4R gene are associated with LIF mRNAs and protein expression levels [48] and variations of LIF gene are association with the recurrent abortions in women [47] and litter size traits in sows [10]. This evidence suggests that the IL-4R gene may be implicated in litter size traits in pigs.…”
Section: Discussionmentioning
confidence: 91%
“…The decreased VEGF and IL-4 expression levels are associated with recurrent spontaneous miscarriage or recurrent abortion in women [49], and the decreased LIF and IL-4 cytokines of decidual T cells are associated with unexplained recurrent abortions [47]. Moreover, the polymorphisms of LIF and VEGF genes are associated with litter size traits in pigs [10,14]. This evidence suggested that the IL-4 gene may contribute to embryonic implantation and be related to litter size traits in pigs.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Also leukemia inhibitory factor (LIF), interleukin-6 (IL-6) and interleukin-11 (IL-11), and its receptor (IL-11Ra) have unquestionable roles in the implantation process [105][106][107]. Studies in pig have reported an association between certain polymorphisms in LIF gene with the number of piglets [108][109][110][111].…”
Section: Cytokinesmentioning
confidence: 99%